The Effectiveness of Anger Management Education in College Students Majoring in Sports (Sains Humanika, 2025)
This study reports on the actual situation of stress coping among college students majoring in sports and the effectiveness of their educational approach. A performance may decrease for the anger that an athlete cannot control as a background of the problem. In addition, it is demanded that the member of society builds human relations without the harassment, and, as for the university student, a skill of the feelings control is demanded from the society. The subjects were 132 college students majoring in sports and psychosocial studies. Their ages ranged from 19 to 22 years old. The purpose of the study was to “recapture past anger experienced by the self and to build a foundation for improving the performance of that anger in the future. The educational intervention will be conducted a total of five times at 90 minutes per session. The results suggested that the university students' mental health was good, with many sports-related behaviors as stress coping. In order to compare the educational effects, the anger and aggression questionnaire was measured at the beginning of the second session and at the end of the fifth session, and a corresponding t-test was conducted. The results showed a significant increase in post physical aggression over pre (t=-2.40, p
Keywords: Anger management education, anger control, anger of college students